Marketing ambiental nos postos de combustíveis no município de São Gabriel – RS - Lederhos, Thaise Goulart; Barata, Ana Júlia Senna Sarmento; Alves, Ricardo Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In order to minimize the environmental problems caused by pollution, public, private and third sector organizations began adopting environmental marketing strategies as a tool to meet a growing demand from concerned stakeholders with the environmental crisis. Among the many organizations that cause negative environmental impacts and that are regulated by environmental agencies, stand out the gas stations. Thus, this study aimed to characterize the environmental marketing actions taken by municipal gas station São Gabriel - RS. Several interviews were conducted with managers of the city’s gas stations. It was found in relation to environmental issues: employees are aware about the environmental problems; at gas stations reusing water is not made used in car washes or rainwater harvesting; the posts there is a suitable place for storage of materials and waste, and these are stored in covered places and their packaging is made in resistant and sealed containers; all stations have contingency plans to minimize leakage of fuel, offering trained staff in case of situations like explosions, accidents in normal operations or products leak. There are many differences between the perceptions of managers in relation to environmental issues, however, the results revealed that the São Gabriel municipality of gas stations - RS work within the standards set by legislation, since adopt all measures required by the inspectors in the environmental context.